Padrões de ordenação de constituintes das construções V2/V3 superficiais em cartas pessoais brasileiras dos séculos 19 e 20 - Moura, Rafael Aguiar (2015)
In line with the model of grammar competition (Kroch, 1989; 2001), according to which the change in the syntactic domains is a process that develops via competition between different grammars, we describe and analyze the superficial constructions V2 / V3 in matrices / roots sentences of brazilian personal letters of the 19th and 20th centuries. The corpus, composed by 154 personal letters of Rio de Janeiro and Rio Grande do Norte, is divided into three century halves: (i) latter half of the 19th century; (ii) first half of the 20th century; and (iii) latter half of the 20th century. Our focus was the observation of the nature of preverbal constituents in superficial constructions V2 (verb in second position in the sentence) and V3 (verb in third position in the sentence), with a special attention on the position of the subject. Based on the various diachronical studies about the Portuguese ordination standards (Ambar (1992); Ribeiro (1995, 2001); Paixão de Sousa (2004); Paiva (2011), Coelho and Martins (2009, 2012)), our study sought to realize what are empirical ordination standards that involve superficial constructions V2 / V3 and how these patterns structure syntactically within a formal theoretical perspective (Chomsky, 1981; 1986), more specifically, in accordance with studies of Antonelli (2011), and Costa & Galves (2002). The survey results show that the data from the second half of the 19th century – unlike the first and second half of the 20th century data – have a greater balance in relation to the syntactic nature of preverbal constituent (contiguous or not), so that, in this period, the occurrence of orders with the subject in a preverbal position arrives at, at most, 52% (231/444 data); while in the 48% (213/444 data) remaining, the preverbal constituents are represented by a non-subject constituent, almost always an adverbial adjunct. Seen the results, we advocate that the brazilian personal letters of the 19th century have ordination patterns associated with a V2 system and an SV system, configuring, therefore, a possible competition process between different grammars that instantiate or a V2 system or an SV system. In other words, the brazilian letters of the 19th century instantiate a competition between the grammar of Classic Portuguese (a V2 system) and the grammars of Brazilian Portuguese and European Portuguese (an SV system). Therefore, that period is subject to the completion of two distinct parametric markings: (i) verb moved to the Fin core (grammar of Classic Portuguese) and (ii) verb moved to the T core (grammar of Brazilian Portuguese /European Portuguese). On the other hand, in the personal letters of the 20th century (first and second halves), there is a clear increase in ordenation patterns associated with the SV system, which shows more stable.